A study on factors that motivate employee to work a case study at Melaka Police Contingent Headqurters Melaka / Amir Muzakkir Omar and Azmi Shafiq Abd Rahman - Omar, Amir Muzakkir; Abd Rahman, Azmi Shafiq (Faculty of Administrative Science and Policy Studies, 2014)
This research is about factors that motivate employee to work at Melaka Police Contingent Headquarters. The objectives of this research are to determine relationship between rewards and recognition, employee participation, job assignment and motivation to work. About 136 respondents were selected as sample size of this research. Convenience sampling technique was used when selected the 136 respondents at Melaka Police Contingent Headquarters. The respondents were required to answer questionnaire that consists of 48 questions include 5 demographic section. The researcher use Descriptive statistic, Cronbach’s Alpha and Spearman rank Order Correlation to analyze the data gathered using Statistical Package for Social Science (SPSS) Version 20.0. The result indicates that there are positive correlations between team determinant factor and productivity.